Potential of Cassia auriculata and Saraca asoca standardized extracts and their principal components for alleviating diabetic complications - Ajmera Rama rao,; Ciddi veeresham,; Kaleab Asres, (International Journal of Phytomedicine, 2012)
Aldose reductase (AR) enzyme and advanced glycation endproducts (AGEs) play an important role in diabetic complications such as cataracts. The purpose of this study was to look into two standardized plant extracts used in Ayurvedic medicine for the treatment of diabetes, and their principal components for AR and AGEs inhibitory activities, and to evaluate their potential in combating the various pathological consequences of diabetes. Cassia auriculata Linn and Saraca asoca (Roxb.) De Wild and their respective major constituents, proanthocyanidin B1, and leucocyanidin were studied for their inhibitory activity against rat lens AR (RLAR), rat kidney AR (RKAR), human recombinant AR (HRAR), and generation of AGEs. In addition, in vivo inhibition of lens galactitol accumulation by the major constituents of the plants in galactose-fed rat model has been studied. The results show that both plant extracts and their principal components possess AR inhibitory actions in both in vitro and in vivo assays, and also inhibited AGEs formation significantly. In all assays carried out, proanthocyanidin B1 was found to be the most potent showing comparable or better effect than the reference compounds used. In both RP-HPLC and GLC analyses, rat lens galactitol concenration of procyanidin B1 ( 1.5, 1.6 mg/ml, respectively) displayed a slightly better activity than the reference compound quercetin (1.65, 1.63 mg/ml, respectively). The results obtained in this study give a new dimension to the hitherto unknown activity of the plants as possible protective agents against long-term diabetic complications.